(untitled) (Progress Annals: Journal of Progressive Research, 2023)
The effectiveness of prosthetic methods for restoring mandibular defects is directly dependent on the size and topography of the defect, the number of missing teeth and the condition of the remaining teeth, and the presence and nature of previous reconstructive and restorative surgical treatment. Prosthetics for patients with defects in the alveolar process and mandible with preserved bone continuity may be performed with either removable or fixed prostheses. In clinical cases involving defects up to four teeth in length, bridges with two or more abutments are used at the margins of the defect, with the intermediate portion in the form of a gingival mask made of pink plastic or ceramic and mandated to preserve flush space. Large-area defects are restored with a removable structure featuring a larger artificial gingival size in the alveolar defect area and a supportive retention device splinted to the remaining teeth.